2017
DOI: 10.3390/en10070875
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Recycling Double-Pass V-Corrugated Solar Air Collectors

Abstract: Abstract:The influence of recycling on double-pass solar air collectors with welding of the V-corrugated absorber has been studied experimentally and theoretically. Welding the V-corrugated absorber and the recycle-effect concept to the solar air collector was proposed to strengthen the convective heat-transfer coefficient due to turbulence promotion. Both the recycle effect and the V-corrugated absorber can effectively enhance the heat transfer efficiency compared to various designs such as single-pass, flat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Furthermore, the lowest collector efficiency improvements were found to take place when employing Type A [33], as shown in Table 4, and resulted in a less thermally efficient configuration among all the proposed external-recycle configurations. The extents of collector efficiency improvements were more significant with the recycle ratios than those in the V-corrugated device of the same operational conditions [41]; thus, a higher value of IC,A/IP,A is obtained by operating double-pass cross-corrugated solar air collectors with external recycling, as demonstrated in Figure 15. With those comparisons, the advantage of the cross-corrugated design for solar air collectors is evident.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the lowest collector efficiency improvements were found to take place when employing Type A [33], as shown in Table 4, and resulted in a less thermally efficient configuration among all the proposed external-recycle configurations. The extents of collector efficiency improvements were more significant with the recycle ratios than those in the V-corrugated device of the same operational conditions [41]; thus, a higher value of IC,A/IP,A is obtained by operating double-pass cross-corrugated solar air collectors with external recycling, as demonstrated in Figure 15. With those comparisons, the advantage of the cross-corrugated design for solar air collectors is evident.…”
Section: Resultsmentioning
confidence: 90%
“…It is evident that the cross-corrugated double-pass solar air collector delivers greater economic and technical feasibility due to a greater and useful energy gain, albeit at the expense of a reduced amount of power consumption, as shown in Figures 13-15. The extents of collector efficiency improvements were more significant with the recycle ratios than those in the V-corrugated device of the same operational conditions [41]; thus, a higher value of I C,A /I P,A is obtained by operating double-pass crosscorrugated solar air collectors with external recycling, as demonstrated in Figure 15. With those comparisons, the advantage of the cross-corrugated design for solar air collectors is evident.…”
Section: Discussionmentioning
confidence: 89%
“…It was also noted that enhancing the wind velocity and Reynold number caused a reduction in the overall temperature of the collector. Ho and Hsiao [117] found that the performance of SACs was enhanced using a V-groove stainless steel absorber, and the recycling ratio increased from 0.25 to 2. El-Sebaii and Aboul-Enein [37] found that the overall heat losses were reduced using a V-corrugated solar air collector compared to a Zulkifle and Alwaeli [116] found that the Fresnel lens outperformed the glass cover in terms of the outlet air temperature and thermal efficiency using a V-groove as the absorber.…”
Section: 𝑒 𝐷mentioning
confidence: 99%
“…Another way for enhancing heat transfer is using baffles with different shapes, such that this technique was examined by Bayrak (2013), El-Said (2020), Fiuk (2019), Hachemi (1995), Chabane (2014) and Yang (2014). Replacing flat plate absorber with V-groove corrugated absorber is another method for performance improvement and many investigators including Ho (2017), Desisa (2020) and El-Sebaii (2011) studied about this technique. A numerical analysis of solar air dryer with a V-groove double pass collector carried out by Hassan (2022) and the obtained findings which revealed the positive effect of the applied method were validated with experiment.…”
Section: Introductionmentioning
confidence: 99%